Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae) - Tauber, Catherine A.; Sosa, Francisco; Contreras-Ramos, Atilano (Zootaxa, 2018)
The green lacewing genus name Cryptochrysa Freitas & Penny 2001 is identified as a junior homonym of Cryptochrysa Hampson 1926 (Lepidoptera: Noctuidae). Moreover, Titanochrysa Sosa & Freitas 2012 is determined to be an available junior synonym of Cryptochrysa Freitas & Penny. Thus, Titanochrysa becomes the substitute name for the preoccupied generic name. Here, we also provide (i) new information and images for Titanochrysa chloros (Freitas & Penny) comb. nov., the only species ever included in the chrysopid genus Cryptochrysa, (ii) a clarified set of diagnostic features for the reconstituted genus Titanochrysa, and (iii) a key and images for identifying the six described Titanochrysa species.